POTENSI EKOSISTEM HUTAN MANGROVE TERHADAP KEBERADAAN MADU HUTAN SEBAGAI JASA LINGKUNGAN DI DESA BATU AMPAR KABUPATEN KUBU RAYA - Sihotang, Orind K; Hardiansyah, Gusti; Wardenaar, Evy (JURNAL HUTAN LESTARI, 2019)
Mangrove forest ecosystem is a place to live living things and plants that live in the tidal area of the sea. For coastal communities the presence of mangrove honey is very beneficial, especially for fishermen. Because mangrove forests are their place of livelihood, one of them is forest honey which can increase their economic growth. Not only that mangrove forests provide a lot of environmental services that can play an important role in their survival as well as the environment around them and have a considerable impact on the current climate conditions of the world. The research aims to see how the potential of the mangrove ecosystem towards the existence of forest bees. As well as the availability of feed or flower extract nectar in the mangrove forest area that is needed as forest bee food and the value of benefits for forest honey farmers to the presence of forest bees (Apis Dorsata) in Batu Ampar Village, Kubu Raya Regency. This study uses a survey method by looking directly at the honeycomb attached to each tree. The results showed that the relative frequency of mangrove forests was 100%. For the relative abundance obtained at 17% while the actual dominance is 100% with INP 2.17. While the total benefit value is Rp.476,141,924 with moderate levels of diversity. Mangrove forests provide the role of ecosystems in the presence of forest bees (Apis dorsata) in attaching their nests to nyiri trees (Xylocarpus granitus). For bee feed is found in nipah (Nypa) which has complete flowes are on the nypa has full flower.Keywords: Forest Bee, Mangrove Ecosystem